Microcomputers in business : WordStar, dBase II and III, and Lotus 1-2-3 - Spence, J. Wayne; Windsor, John C. (St. Louis, Missouri : Times Mirror/Mosby College Publishing, 1987)
This course is typically taught at the freshman or sophomore level in two- or four-year colleges and is typically aimed at business majors, information systems majors, and MBAs.
Overview: Microcomputer applications in business I -- Module One. Processing wordstar -- Modules Two. Database: dBase II and III -- Module Three. Spreadsheet, database, and graphics: Lotus 1-2-3.
Includes bibliographical references and index.
Keywords: BUSINESS -- DATA PROCESSING